2015
DOI: 10.1590/1678-476620151053307315
|View full text |Cite
|
Sign up to set email alerts
|

Biologia reprodutiva de Macrobrachium jelskii (Crustacea, Decapoda, Palaemonidae) no Rio São Francisco, Minas Gerais, Brasil

Abstract: ABSTRACT. Reproductive biology of the shrimp Macrobrachium jelskii (Crustacea, Decapoda, Palaemonidae) in São Francisco River, Minas Gerais, Brazil. The objective was evaluate the reproductive biology of Macrobrachium jelskii (Miers, 1877) The netting mouth had 1 m² and the mesh 1.42 mm that it was passed under the marginal vegetation and the water next to the bank during 30 minutes. In the laboratory, specimens were identified, measured and sexed. A total of 2,945 specimens were captured in the upstream, 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
(16 reference statements)
1
10
0
3
Order By: Relevance
“…However, these last authors concluded that the male biased sex ratio in lotic environment occurred because females seek shelter among marginal vegetation, which was abundant downstream the Três Marias Dam. Therefore, most available information on M. jelskii populations show that a female biased sex ratio is the most frequent condition (Gamba, 1997;Barros-Alves et al, 2012;Soares et al, 2015; this study).…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…However, these last authors concluded that the male biased sex ratio in lotic environment occurred because females seek shelter among marginal vegetation, which was abundant downstream the Três Marias Dam. Therefore, most available information on M. jelskii populations show that a female biased sex ratio is the most frequent condition (Gamba, 1997;Barros-Alves et al, 2012;Soares et al, 2015; this study).…”
Section: Discussionmentioning
confidence: 64%
“…Specifically in the case of M. jelskii, rainfall and water temperature play key roles in establishing the reproductive period, as several authors have noted the intensification of the reproductive activity during the warmer and humid months (Gamba, 1997;Lima et al, 2013;Mossolin et al, 2013;Soares et al, 2015;present study).…”
Section: Population Biology Of Macrobrachium Jelskii From Bahiamentioning
confidence: 78%
See 3 more Smart Citations